Modified: Hubble’s Law - Dialynas, Thanassis E. (European Journal of Applied Sciences, 2024)
Based on natural grounds, we propose a (special - relativistic) “modification” of Hubble’s Law [6, 7, 8, 9]. The advantage is that no galaxy can exceed the speed of light, no matter how far it is. The disadvantage is that the equations appearing are more difficult to handle and they are also non – invertible. The main tendencies of the “theory” [8] remain the same.